PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SEPHORA DENGAN GAYA HIDUP SEBAGAI VARIABEL INTERVENING - Puspitasari, Mita; Budiarti, Anindhyta (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
A beauty product is a kind of product that is needed to take care of and beautify skin and personal performance. Moreover, in Indonesia, the growth of the cosmetics market is also planned to rise 7% in 2021. Therefore, Sephora introduced various beauty products that are offered. In line with that, its unique open retailer environment shows more brands in the products category, including skincare, cosmetics, perfume, body treatment, hair treatment, and many more to complete the label. This research aimed to find out and analyze the effect of brand image and product quality on the lifestyle of purchasing decisions. Additionally, the research was comparative-quantitative. The result concluded that the more increased and stronger the product’s brand image in Sephora was, the more increased the lifestyle of consumers would be. Likewise, the more product quality was, the more the product purchasing decisions would be. However, higher the lifestyle of Sephora won’t increase the consumers’ purchasing decisions.